(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Information literacy skills and digital information resources are essential for students’ development to enhance their academic activities. This study examined information literacy skills and digital information resources on academic activities of University Students in Nigeria. Survey research design was adopted for the study. The population for this study comprised 7020 students. 5,324 from Lead City University and 1,696 from Mountain University. Stratified sampling technique was adopted. The sample size was 400 respondents. Data were analyzed using descriptive and inferential statistics. The result shows that Information literacy skills enable students to recognize different methods of accessing electronic 163 (41.7%); ILS enable students to judge the accuracy and authenticity of website information 145 (37.1%). Majority of the students fully utilized internet access 197 (47.8%), computer system and personal data 178 (45.8%). The students' level of information literacy and their use of digital information resources influence their academic activities. The library management should strive to obtain up-to-date digital resources, provide extensive internet access bandwidth, and ensure an ample supply of computer systems and electronic reference sources.